2013
DOI: 10.1590/s1415-790x2013000400001
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence among undergraduate students of two universities of the state of São Paulo, Brazil

Abstract: Introduction: The prevalence of violence in intimate relationships, suffered or perpetrated, was estimated among undergraduate students, be it physical, psychological and sexual, describing the overlap between them. This is an original study and there is scarce literature on this matter in Brazil. Men and women were investigated and some issues on gender violence were discussed. Methods: The study is part of the multicenter survey "International Study of Violence in Dating -IDVS" conducted in 2002 -2003, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
19

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 23 publications
1
9
0
19
Order By: Relevance
“…For example, using the same instrument to assess sexual victimization, two studies in the five major regions of Brazil found similar rates of lifetime female sexual victimization (13% in 2004 23 and 10% in 2010 24 ). Studies that used CTS2 in university students also found similar previous-year incidence rates, ranging from 39% to 40% in women and 30% to 37% in men 38,39,40 . Of the twelve studies that adopted the WHO questionnaire, three found similar lifetime prevalence rates for sexual victimization, varying from 9.8% to 11.8% in São Paulo State 13,26,41 .…”
Section: • Definition Of Sexual Victimizationmentioning
confidence: 63%
See 4 more Smart Citations
“…For example, using the same instrument to assess sexual victimization, two studies in the five major regions of Brazil found similar rates of lifetime female sexual victimization (13% in 2004 23 and 10% in 2010 24 ). Studies that used CTS2 in university students also found similar previous-year incidence rates, ranging from 39% to 40% in women and 30% to 37% in men 38,39,40 . Of the twelve studies that adopted the WHO questionnaire, three found similar lifetime prevalence rates for sexual victimization, varying from 9.8% to 11.8% in São Paulo State 13,26,41 .…”
Section: • Definition Of Sexual Victimizationmentioning
confidence: 63%
“…The highest previous-year incidence rate was reported by a sample of university students (38.5% in women and 34.5% in men) 38 . Three other studies also reported high victimization rates in university students 14,39,40 .…”
Section: • Regionmentioning
confidence: 85%
See 3 more Smart Citations